PERANAN MODEL PEMBELAJARAN CIRC BERBASIS KARAKTER TERHADAP KOMPETENSI PENGETAHUAN AGAMA HINDU SISWA KELAS IV SDN GUGUS PATTIMURA DENPASAR SELATAN TAHUN PELAJARAN 2021/2022 - Rai Sawitri, Ni Nyoman (JAPAM (Jurnal Pendidikan Agama), 2024)
The purpose of this study was to determine the effect of the character-based cooperative integrated reading and composition (CIRC) learning model on the knowledge competence of Hinduism in fourth grade students of SDN Gugus Pattimura, South Denpasar, in the 2021/2022 academic year. This type of research is qualitative research. Qualitative data is usually obtained from subjective interviews because the data is estimated by different people. The approach used in this study is a qualitative approach. This research was conducted at SD Negeri 2 Ketewel, Ketewel Village, Sukawati District, Gianyar Regency. Other data sources are people who in qualitative research are called informants. Informants selected by purposive sampling. Purposive sampling is a sampling technique with certain considerations. In this qualitative research, the research instruments used are: tape recorder, open questionnaire, interview guide and descriptive notes. Data collection techniques in this study include observation, interviews, documentation studies and literature studies Keywords: Cooperative integrated reading and composition, Character, Hindu religious knowledgecompetence